Pemanfaatan Generatif AI dalam Pembelajaran Bahasa untuk Siswa SD: Pendekatan Inovatif dalam Meningkatkan Kemampuan Menulis - Tri Syamsi Julianto; Stelie Ratumanan (Bima Journal of Elementary Education, 2023)
This research explores the importance of utilizing Generative Artificial Intelligence (AI) in language learning for Elementary School (SD) students. The research aims to identify whether the use of Generative AI can enhance the writing skills of elementary school students. The study was conducted with elementary school students from two different schools as the research population located in the Nanga Pinoh District, Melawi Regency. The research sample consists of two classes that used Generative AI in language education, while the other two classes served as the control group. Data analysis techniques included evaluating the students' written work, considering completeness, structure, and creativity. The results of the study show a significant improvement in the writing skills of students who received education with the utilization of Generative AI, demonstrating a substantial enhancement in the completeness, structure, and creativity of their writing compared to the control group. In conclusion, the use of Generative AI in language education for primary school students represents an innovative approach that can significantly enhance their writing skills. The findings of this research provide concrete evidence that Generative AI technology holds great potential for enriching the language learning experience and writing skills of primary school students. Suggestions for further research include the development of more specific and contextual teaching strategies, as well as expanding the range of subjects that can benefit from Generative AI. In this rapidly evolving technological era, further research on the use of AI in primary education will contribute to creating a more innovative learning environment that supports the development of students' language skills.